Public-Private Partnerships: Policy and Regulation: With Comparative and Multi-level Case Studies from Denmark and Ireland - Ole Helby Petersen (Copenhagen Business School (CBS), 2011)
This PhD dissertation studies national similarities and differences in policy and regulation of public-private partnerships (PPPs), with an empirical focus on Denmark and Ireland. The starting point and motivation for the study is the observation that whereas PPPs are often depicted in the academic literature and in policy practice as a globally disseminated governance scheme, in reality, a closer examination of the PPP reform landscape reveals significant differences in national governments' PPP policy and regulation and in the amount of actually implemented PPP projects. By comparing the initiatives taken by the Irish government, which has embraced PPPs, with those of the Danish government, which has been a PPP sceptic, this study inquires into the fundamental questions as to how, why and to what consequences some governments have developed widespread policy and regulation frameworks to support the implementation of PPPs, whereas others have been much more reluctant. The dissertation addressed four research questions: (i) what are the key actors, strategies and institutions that create policies and regulations for the formation of PPPs?; (ii) how did governments' PPP policies and regulations develop over time, and how can their similarities and differences be explained?; (iii) how do differing national policy and regulation frameworks serve to facilitate or hinder the formation of PPPs, exemplified by four case studies from the schools sector?; (iv) what framework conditions does the EU set for PPP initiatives at national and sub-national levels? The main aim of the dissertation is to study how and why national PPP policy and regulation frameworks developed over time. At the national government level, the study thus contains both diachronic and synchronic analysis. Furthermore, in line with previous research within what has been called the governance approach within PPP studies, policy and regulation are also seen as constitutive elements that tap into and set the general framework conditions and institutional `rules of the game' for the realisation of concrete PPP projects. The comparative interest at the central government level is thus supplemented by an analysis (a) of the interplay between decisions about policy and regulation at the national level and the formation of concrete PPP projects, and (b) of the EU's role in regulating decisions about PPPs at national level and in relation to the formation of concrete PPP schemes. A main finding is that whereas academic PPP literature often portrays governments' rationales for resorting to PPPs in terms of achieving innovation, collaborative advantage, value-for-money, new market possibilities, improved risk sharing etc., the findings brought to the fore in this dissertation suggest that a primary objective indeed was to remove major public infrastructure investments from governments' balance sheets, and thereby reduce the pressure on public capital budgets and provide more infrastructure than would otherwise be possible. However, as the off balance sheet rationale has been shown to be largely false, because there is always a bill to pay in the long term, this raise a number of broader legitimacy and accountability issues, which the present PPP policy and regulation frameworks of governments do not seem to adequately address.
hdl:10398/9114
Keywords: 650